2018
DOI: 10.1103/physrevb.97.195432
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and environmental effects on the interference properties of a high-performance quantum dot single-photon source

Abstract: We report a joint experimental and theoretical study of the interference properties of a single-photon source based on a In(Ga)As quantum dot embedded in a quasiplanar GaAs microcavity. Using resonant laser excitation with a pulse separation of 2 ns, we find near-perfect interference of the emitted photons, and a corresponding indistinguishability of I = (99.6 + 0.4 − 1.4 )%. For larger pulse separations, quasiresonant excitation conditions, increasing pump power, or with increasing temperature, the interferen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The QD couples to both vibrational and electromagnetic environments, which results in the total Hamiltonian H = H S + H S–ph + H S–em + H B . At low temperatures the electron−phonon interaction is dominated by a linear displacement coupling with Hamiltonian , where b k () is the annihilation (creation) operator of phonon mode k with frequency ω k and coupling strength g k 24,4749 . The electron−phonon coupling is characterised by the spectral density 24 , with coupling strength ζ and cut-off frequency ω c .…”
Section: Methodsmentioning
confidence: 99%
“…The QD couples to both vibrational and electromagnetic environments, which results in the total Hamiltonian H = H S + H S–ph + H S–em + H B . At low temperatures the electron−phonon interaction is dominated by a linear displacement coupling with Hamiltonian , where b k () is the annihilation (creation) operator of phonon mode k with frequency ω k and coupling strength g k 24,4749 . The electron−phonon coupling is characterised by the spectral density 24 , with coupling strength ζ and cut-off frequency ω c .…”
Section: Methodsmentioning
confidence: 99%
“…State-of-the-art experiments have demonstrated that electron-phonon processes play a crucial role in determining the coherence properties of photons emitted from solid-state quantum emitters [23,46,47]. However, developing a theoretical model to accurately account for such processes remains a significant challenge.…”
Section: Electron-phonon Coupling and Its Signatures In The Optical Ementioning
confidence: 99%
“…Nevertheless, spectral fine-tuning remains the missing tool required to overcome remaining fabrication inaccuracies. Temperature and electrical tuning techniques cause a significant deterioration of the source performance via phonon-induced decoherence [22] and carrier tunneling, respectively [23]. On the other hand, strain tuning techniques allow for reversible shifting of the emitter energies without degrading their optical properties [24,25].…”
Section: Introductionmentioning
confidence: 99%